Should the General Practitioner Consider Mesotherapy (Intradermal Therapy) to Manage Localized Pain? - Mammucari, Massimo (Pain Ther, 2016)
Wide variations in the types of pain and response to analgesic pharmacotherapy mean that a variety of treatment strategies are needed. One approach is mesotherapy (intradermal therapy). This consists of microinjections into the skin and is ideally suited to the management of localized pain. Advantages include increasing the duration of drug activity, reduced risk of adverse events and interactions, and possible synergy with other therapies. Mesotherapy provides general practitioners with another tool for the treatment of local pain. However, it is important to provide patients with full details of the pros and cons of this approach and obtain informed patient consent.